2016
DOI: 10.1111/ijfs.13295
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chitosan coating combined with essential oils on quality and antioxidant enzyme activities of grass carp (Ctenopharyngodon idellus) fillets stored at 4 °C

Abstract: Effects of chitosan coating combined with essential oils from clove, cinnamon and lemon grass on quality and antioxidant enzyme activities of grass carp fillets stored at 4 AE 0.5°C were evaluated. The quality parameters (including pH, total volatile basic nitrogen (TVB-N), K value, thiobarbituric acid (TBA) value, shear force and total viable count (TVC)) and antioxidant enzyme activities were analysed periodically. The results indicated that composite chitosan coatings presented better preservation effects t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 32 publications
6
22
0
Order By: Relevance
“…At Day 12, TVB‐N value of the T4 samples was 22.15, and it has been classified as “the highest acceptable level.” Similar results were found by Ojagh et al (), Wenjiao et al (), Chamanara et al (), and Yu et al (). Ojagh et al () reported that chitosan+cinnamon oil coating reduced the TVB‐N values of rainbow trout fillets.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…At Day 12, TVB‐N value of the T4 samples was 22.15, and it has been classified as “the highest acceptable level.” Similar results were found by Ojagh et al (), Wenjiao et al (), Chamanara et al (), and Yu et al (). Ojagh et al () reported that chitosan+cinnamon oil coating reduced the TVB‐N values of rainbow trout fillets.…”
Section: Resultssupporting
confidence: 90%
“…Chamanara et al () reported that the chitosan coating enriched with thyme essential oil decreased the TVB‐N values of butterfly‐shaped rainbow trout stored under refrigerated condition for 15 days. Yu et al () found lower contents of TVB‐N in chitosan+clove oil coated grass carp fillets during 15 days storage.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that the essential oils obtained from thyme, sage, rosemary, clove, coriander, garlic, and onion have antimicrobial activity and this effect is due to the phenolic compounds found in their structures (Haşimi, Kızıl, & Tolan, ). It has been reported that the combinations of chitosan coatings with volatile oils have a positive effect on fillets, thus extending the shelf life and inhibiting effect of lemon oil applications on microorganism as in our study (Yu, Xu, Jiang, & Xia, ). In another study performed with plant extracts, it was reported that ginger extract inhibited the increase in total bacterial counts (Shi et al, ).…”
Section: Discussionsupporting
confidence: 67%